2013
DOI: 10.1007/jhep01(2013)139
|View full text |Cite
|
Sign up to set email alerts
|

Higgs couplings and precision electroweak data

Abstract: In light of the discovery of a Higgs-like particle at the LHC, we revisit the status of the precision electroweak data, focusing on two discrepant observables: 1) the long-standing 2.4σ deviation in the forward-backward asymmetry of the bottom quark A b F B , and 2) the 2.3σ deviation in R b , the ratio of the Z → bb partial width to the inclusive hadronic width, which is now in tension after a recent calculation including new two-loop electroweak corrections. We consider possible resolutions of these discrepa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 102 publications
(144 reference statements)
3
65
1
Order By: Relevance
“…lines have shown that the coefficients of the leading operators in this expansion can already be meaningfully constrained [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Jhep11(2013)111mentioning
confidence: 92%
See 1 more Smart Citation
“…lines have shown that the coefficients of the leading operators in this expansion can already be meaningfully constrained [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Jhep11(2013)111mentioning
confidence: 92%
“…3 See also [15][16][17][18][19]43] for previous studies of the impact of electroweak precision tests in the context of the 126 GeV Higgs. …”
Section: Jhep11(2013)111mentioning
confidence: 99%
“…Constraints on the corrections to the Z boson couplings to the bottom quark. The ellipses show the exclusion contours at 68% and 95% confidence level [79,80]. The vertical band shows the expected size of the corrections to the g b R coupling.…”
Section: Jhep10(2013)160mentioning
confidence: 99%
“…On the other hand, extensions of the SM with vector-like leptons which couple to the Higgs, can both enhance and suppress the h → γγ decay rate, because in contrast to chiral leptons, vector-like leptons can interfere also constructively with the W contribution. Colored new matter is additionally constrained by data, because it also affects the gluon fusion production cross section of the Higgs, which in turn leads to modifications of all Higgs signal strengths [7,9,14,25,26,28,[43][44][45][46][47].…”
Section: Models With Exotic Hyperchargesmentioning
confidence: 99%